2022
DOI: 10.7150/ijbs.75434
|View full text |Cite
|
Sign up to set email alerts
|

Lactylation of PKM2 Suppresses Inflammatory Metabolic Adaptation in Pro-inflammatory Macrophages

Abstract: Emerging evidence suggests that metabolic adaptation is a vital hallmark and prerequisite for macrophage phenotype transition. Pyruvate kinase M2 (PKM2) is an essential molecular determinant of metabolic adaptions in pro-inflammatory macrophages. Post-translational modifications play a central role in the regulation of PKM2. However, doubt remains on whether lactylation in PKM2 exists and how lactylation modulates the function of PKM2. For the first time, our study reports that lactate inhibits the Warburg eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 64 publications
2
51
1
Order By: Relevance
“…Wang et al investigated the lactylation of PKM2 and confirmed that PKM2 lactylation could suppress inflammatory metabolic adaptation in proinflammatory macrophages. This finding confirmed the result of our analysis, which indicated that the modification site K62 on PKM2 was in the structural domain and may affect the function of the protein [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Wang et al investigated the lactylation of PKM2 and confirmed that PKM2 lactylation could suppress inflammatory metabolic adaptation in proinflammatory macrophages. This finding confirmed the result of our analysis, which indicated that the modification site K62 on PKM2 was in the structural domain and may affect the function of the protein [16].…”
Section: Discussionsupporting
confidence: 91%
“…However, HCC may develop resistance toward these chemicals and targeted drugs, which can attenuate treatment efficacy [2,3]; in addition, the high heterogeneity of HCC has become an obstacle in HCC treatment [4]. Therefore, Pharmaceuticals 2023, 16, 644 2 of 19 developing an effective prognostic model that is useful in selecting proper treatment approaches and drugs for HCC treatment is an urgent issue.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking such vicious feedback mitigates microglial dysfunction and cognitive deficits in AD mouse model 8 . A direct lactylation of PKM2 at lysine 62 (K62) that creates a negative feedback to glycolysis is also proposed 134 . This inhibitory regulation of glycolysis by lactate promotes the transition of proinflammatory macrophages to a reparative phenotype via suppressing their metabolic adaptation 134 .…”
Section: Lactate‐driven Lactylation: a Novel Protein Modification In ...mentioning
confidence: 99%
“…8 A direct lactylation of PKM2 at lysine 62 (K62) that creates a negative feedback to glycolysis is also proposed. 134 This inhibitory regulation of glycolysis by lactate promotes the transition of proinflammatory macrophages to a reparative phenotype via suppressing their metabolic adaptation. 134 Such phenotypic transition of macrophages allows tissue to recover from the inflammatory response.…”
Section: Lactylation: a Novel Protein Modification In Cellular Physio...mentioning
confidence: 99%
See 1 more Smart Citation